(untitled) (Ricos Biology, 2025)
Background and objective: Millions of cases of the COVID-19 pandemic have caused a worldwide health crisis. Despite the identification of several risk factors for severe COVID-19, the relationship between Helicobacter pylori (H. pylori) infection and COVID-19 severity remains uncertain. To clarify this association, a study will be conducted to investigate the possible link between H. pylori infection and COVID-19 severity in patients from Iraq. Methods: A total of 424 COVID-19 patients who were admitted to different hospitals in Iraq from January to July 2022 were included in this retrospective study. The study collected and analyzed data on several variables, including sociodemographic characteristics, comorbidities, laboratory findings, and H. pylori infection status. Results: Of the patient population, 198 individuals (46.7%) identified as male and 226 (53.3%) as female, with an average age of 49.6 years (range: 18-73 years). The majority of patients possessed at least one comorbidity, with hypertension (47.6%), diabetes mellitus (34.2%), and obesity (23.6%) being the most common. Among the patients observed, 101 (23.8%) had an H. pylori infection. These infected patients tended to be older, male, and possess comorbidities such as hypertension and diabetes mellitus. In terms of laboratory findings, patients with H. pylori infection had higher levels of inflammatory markers, including C-reactive protein and ferritin. Furthermore, patients with H. pylori infection had a higher incidence of severe COVID-19, necessitating mechanical ventilation and ICU admission. Conclusions: The results of the study indicate a potential correlation between H. pylori infection and the severity of COVID-19 among patients in Iraq.